Analysis of Turnout Rails Characteristic Section Wear Based on Spatial Alignments Optimization of Guide Curves - LONG Jianbing; XU Hong; ZHANG Bin (Chengshi guidao jiaotong yanjiu)
［Objective］ In order to explore the optimization method of the spatial alignment for the turnout guide curve and the performance of different alignments after optimization, as well as the influence of different alignments on the rail wear characteristic section in the turnout area, it is necessary to study the wear laws of each characteristic section of the turnout rail under different alignment conditions. ［Method］ A calculation method for the turnout plane alignment is proposed. Superelevation is set in the turnout guide curve, and high-order curves are introduced into the design and calculation of turnout alignment. Taking No.42 high-speed turnout in China as an example, four optimized turnout alignments different from the existing ones are designed and calculated; a vehicle-turnout coupling dynamic model is established, and the wear depth of the characteristic sections of the turnout rail is calculated in combination with the wheel-rail contact finite element model. A comparative analysis is made on the wear depth of the characteristic sections of the turnout rail under different line shape conditions. ［Result & Conclusion］ Under the condition of setting superelevation, wear depths at three characteristic sections of the four new alignments are all smaller than that of the existing ones; after changing the lead curve from a circular curve to a transition one, wear depths of the rail characteristic section in this guide curve are also greatly reduced; the application of high-order curves at the position of the turnout guide curve is also conducive to reducing the wear of the characteristic section in the selected guide curve rail.